Division of Labor Brings Greater Benefits to Clones of Carpobrotus edulis in the Non-native Range: Evidence for Rapid Adaptive Evolution - Roiloa, Sergio R.; Retuerto, Rubén; Campoy, Josefina G.; Novoa, Ana; Barreiro, Rodolfo (Frontiers in Plant Science, 2016)
Why some species become invasive while others do not is a central research request in biological invasions. Clonality has been suggested as an attribute that could contribute to plant invasiveness. Division of labour is an important advantage of clonal growth, and it seems reasonable to anticipate that clonal plants may intensify this clonal attribute in an invaded range because of positive selection on beneficial traits. To test this hypothesis, we collected clones of Carpobrotus edulis from native and invasive populations, grew pairs of connected and severed ramets in a common garden and under negative spatial covariance of nutrients and light to induce division of labour, and measured biomass allocation ratios, final biomass and photochemical efficiency. Our results showed that both clones from the native and invaded range develop a division of labour at morphological and physiological level. However, the benefit from the division of labour was significantly higher in apical ramets from the invaded range than in ramets from the native area. This is a novel and outstanding result because it provides the first evidence that the benefit of a key clonal trait such as division of labour may have been subjected to evolutionary adaptation in the invaded range. The division of labour can therefore be considered an important trait in the invasiveness of C. edulis. An appropriate assessment of the influence of clonal traits in plant invasions seems key for understanding the underlying mechanisms behind biological invasions of new environments.